2016
DOI: 10.1038/srep19081
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pathogenicity and immunogenicity of Mycoplasma mycoides subsp. mycoides strains revealed by comparative genomics analysis

Abstract: Mycoplasma mycoides subsp. mycoides is the causative agent of contagious bovine pleuropneumonia. A pathogenic strain BEN-1 was isolated from bovine lung and underwent continuous passages in rabbits for 468 generations. During this process, the strain’s strong virulence became weak and, gradually, it lost the ability to confer protective immunity in cattle but developed virulence in rabbits. In order to gain insight into the mechanisms behind the reduction in virulence and the loss of immunogenicity, we sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
3
8
0
1
Order By: Relevance
“…IL-1β regulation by the NF-κB signaling pathway plays an important role in shaping the inflammatory response against pathogens 8 . Previous reports indicated that after 2 μg/mL Mycoplasma bovis -derived LAMPs stimulation, the expression of IL-1β reached the peak at 12 h. In this study, we found that 1 μg/mL of Mmm-derived LAMPs could stimulate IL-1β expression to the peak levels at 6 h. Although the disease caused by Mmm and M. bovis exhibited similar clinical symptoms and pathological anatomy 4 , 6 8 , the expression kinetics of IL-1β in Mmm-derived LAMPs-stimulated EBL cells were different from M. bovis -derived LAMPs-stimulated EBL cells.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…IL-1β regulation by the NF-κB signaling pathway plays an important role in shaping the inflammatory response against pathogens 8 . Previous reports indicated that after 2 μg/mL Mycoplasma bovis -derived LAMPs stimulation, the expression of IL-1β reached the peak at 12 h. In this study, we found that 1 μg/mL of Mmm-derived LAMPs could stimulate IL-1β expression to the peak levels at 6 h. Although the disease caused by Mmm and M. bovis exhibited similar clinical symptoms and pathological anatomy 4 , 6 8 , the expression kinetics of IL-1β in Mmm-derived LAMPs-stimulated EBL cells were different from M. bovis -derived LAMPs-stimulated EBL cells.…”
Section: Introductionsupporting
confidence: 53%
“…Mmm enters and colonizes respiratory epithelial cells of cattle when they inhale aerosols in contaminated air 4 , 16 . We previously determined that the P19 protein contributes to Mmm adherence to EBL cells 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the adaptive tuning of mutation rates has been documented using laboratory evolution experiments of microorganisms adapting to new conditions (31,35,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). For instance, one long-term experimental evolution on Escherichia coli adapting to a new medium shows its mutation rate is increased by approximately 150-fold, and then reduced up to 60 % by increased adaptation (39).…”
Section: Rise and Fall Of Mutation Ratementioning
confidence: 99%
“…Ecological studies show that increased investments into reproduction and lifespan may not always lead to increases of individual fitness, but their contributions to individual fitness will eventually decrease to virtually zero due to ecological constraints, leading to selection against further investments (23)(24)(25)(26). In particular, long-term studies on experimental evolution demonstrate that organismal evolution is subject to decreased fitness returns with increased adaptations in constant environments (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40); meanwhile, mutation rates also exhibit adaptive tuning with an initial increase and subsequent decrease as the putative adaptation peak is achieved (31,35,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Moreover, one laboratory-based evolutionary study demonstrates a transition from selective evolution to neutral evolution with increased adaptation (34).…”
Section: Introductionmentioning
confidence: 99%